The Character Value Education Analysis in Pakpak Folklore on Indonesian Language Learning - Ceing Suwarni; Rosliani Rosliani (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
The convenience provided by internet technology causes students to be lazy about reading books and prefer to access them through search engines. Students also care less about the environment. In addition, the negative impact caused is decreased student discipline. This study aims to describe the value of the folklore characters in the book "Pakpak Folklore". This type of research is descriptive using a case study design. The research procedure includes the preparation stage, the implementation stage, and the completion stage. Sources of research data are the book "Pakpak Folklore" and the results of interviews conducted by researchers with grade VI teachers. The data collection technique carried out consisted of observation, interviews, and documents. From the research results it is known that in the fairy tales contained in the book "Pakpak Folklore" contains 11.11% religious character values, 11.11% disciplinary character values, 16.67% hard work character values, 11.11% creative character values, 16.67% independent character values, 11.11% curiosity character values, 11.11% communicative character values, 11.11% peace loving character values, 5.56% social caring character values and 16.67% character values responsible. The conclusion of this research are (1) the character values found are 22 character values. (2) the purpose of teaching character values through Pakpak folklore is to develop the potential for the conscience, and affective of students, develop habits and behavior of students, and develop the ability of students to become disciplined, independent and creative humans.